Development of Compact On-Line Partial Discharge Analyzer Assessing Nanocomposite Insulation Performance for Research Purpose - Aulia .; Yanuar Z. Arief; Zulkurnain Abduk-Malek; Zuraimy Adzis; Nor Asiah Muhamad; Muhammad Abu Bakar Sidik; Zainuddin Nawawi (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
Analyzing on-line partial discharge (PD) data using commercially available spreadsheet application software like Microsoft Excel is possible but very difficult to do. The problem is because the PD data are quite long and depend on the sampling rate used during testing. Increasing the sampling rate will increase data samples in one cycle of 50 Hz waveform, and longer time is needed to analyze the data. A further problem is associated with compiling the PD data; Excel uses a large memory to run, plot and calculate the PD data for analysis purpose, and sometimes this leads to computer memory crash. Due to this problem, an alternative on-line PD analyzer (on-LPDA) needs to be developed. This paper reports on the performance of the software that was developed using LabViewTM 8.5. The result shows that the software can extract PD parameters like PD numbers, PD magnitude, and plotting PD pattern without large time and memory consumption, compared with Excel, and experiences no memory crash up to 125 mega sampling (MS) rate.